2016
DOI: 10.1002/ajh.24369
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety results of taliglucerase alfa up to 36 months in adult treatment‐naïve patients with Gaucher disease

Abstract: Taliglucerase alfa is an intravenous enzyme replacement therapy approved for treatment of type 1 Gaucher disease (GD), and is the first available plant cell–expressed recombinant therapeutic protein. Herein, we report long‐term safety and efficacy results of taliglucerase alfa in treatment‐naïve adult patients with GD. Patients were randomized to receive taliglucerase alfa 30 or 60 U/kg every other week, and 23 patients completed 36 months of treatment. Taliglucerase alfa (30 U/kg; 60 U/kg, respectively) resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Key efficacy findings from the taliglucerase alfa phase 3 clinical studies are summarized in Table 2 [ 15 – 21 ], with additional efficacy results shown in Table 3 (treatment-naïve patients) [ 15 , 17 , 18 , 20 , 21 ] and Table 4 (treatment-switched patients) [ 16 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key efficacy findings from the taliglucerase alfa phase 3 clinical studies are summarized in Table 2 [ 15 – 21 ], with additional efficacy results shown in Table 3 (treatment-naïve patients) [ 15 , 17 , 18 , 20 , 21 ] and Table 4 (treatment-switched patients) [ 16 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen patients were found to have anti-taliglucerase alfa antibodies on at least one post-baseline visit; two of these patients were found to have neutralizing antibodies, but efficacy did not appear to be impaired by the development of neutralizing antibodies [ 18 ]. In Study PB-06-003 [ 18 ], the numbers of patients reported to develop anti-taliglucerase alfa IgG antibodies were higher than those reported in previous, shorter term studies [ 8 , 15 ]. This was likely attributable to increased assay sensitivity due to assay modifications that resulted in differences in antibody sample positivity reporting.…”
Section: Introductionmentioning
confidence: 99%
“…11 Untreated patients with GD may have reduced quality of life relative to population norms, 20 and the clinical benefits of enzyme-replacement and substrate reduction therapies in treatment-naïve patients with GD are well established. [21][22][23][24][25][26][27][28][29] The diagnostic guidance in Table 4 is deliberately limited to major factors, but our wider findings could inform Signs and co-variables that did not meet the threshold for importance (a score of ≥3 by >75% of respondents) were classified as minor and not taken forward to round 3 for agreement rating. Signs and co-variables that met the threshold for agreement in round 3 (a score of ≥4 by >67% of respondents) were classified as major; any that did not meet this threshold were classified as minor.…”
Section: Discussionmentioning
confidence: 99%
“…However, delaying treatment can lead to worse outcomes, poorer prognoses and the development of preventable late‐onset complications . Untreated patients with GD may have reduced quality of life relative to population norms, and the clinical benefits of enzyme‐replacement and substrate reduction therapies in treatment‐naïve patients with GD are well established …”
Section: Discussionmentioning
confidence: 99%
“…Taliglucerase alfa, the first plant-cell expressed human recombinant therapeutic protein, is the third ERT approved for the treatment of adults and children with type 1 GD (Shemesh et al 2015 ; Stirnemann et al 2017 ). Its safety and efficacy have been demonstrated in three double-blind two-dose (30 and 60 units/kg EOW) comparative clinical trials: treatment-naïve adults (Zimran et al 2016 ), treatment-naïve children (Zimran et al 2015 ), and in a switch-over trial with both adult and pediatric patients who had been previously treated with imiglucerase (Pastores et al 2014 ). In all these trials (as in other trials of ERTs for GD), efficacy endpoints were a reduction in spleen and liver volumes and improvement in hematological parameters, whereas the impact on bones has been considered exploratory because of the slower response of the skeleton to alglucerase and to imiglucerase (Lebel et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%